2020
DOI: 10.1088/2050-6120/ab7783
|View full text |Cite
|
Sign up to set email alerts
|

An eco-friendly fluorometric polymer nanoparticle for selectively monitoring sulfadiazine in tap water

Abstract: An eco-friendly fluorescence polymer nanoparticle based on carbon quantum dots and poly(methyl methacrylate) nanoparticles is successfully fabricated to detect sulfadiazine. By making use of the abundant functional group of carbon quantum dots and poly(methyl methacrylate) nanoparticles, without any extra modification, the synthetic process of the fluorescence nanoparticles is reduced and the unnecessary chemical molecules are avoided being brought into the reaction system. The investigation of the fluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The PMMA microspheres were prepared by the soap‐free method with some modifications [21]. A typical step is described as follows: methyl methacrylate (10 mL) and water (80 mL) is added to a three‐necked flask and stirred at 600 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…The PMMA microspheres were prepared by the soap‐free method with some modifications [21]. A typical step is described as follows: methyl methacrylate (10 mL) and water (80 mL) is added to a three‐necked flask and stirred at 600 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the performance efficiency of the proposed smart QD@MIP in comparison with the QD@NIP, the smart material was applied for the quantification of sulfadiazine in three animal-based food samples: milk, honey and eggs. To conduct this analysis, aliquots of the food samples were pre-treated and enriched with SDZ solutions with known concentrations of 10.0, 30.0 and 60.0 ppm (Table 4); the experiments were performed using a 3.0 mL sample volume and an optimized interaction time and pH [33][34][35][36][37]. The results obtained from the recovery studies were found to be satisfactory for all the food samples investigated.…”
Section: Application Of the Qd@mip In Real Samplesmentioning
confidence: 99%
“…Compared with other materials, quantum dots (QDs) have outstanding photoelectric performance, and have received considerable public attention. [1][2][3][4] QDs have been widely used in environmental pollution analysis in recent decades. [5][6][7] The synthesis technology of QDs has been rapidly developed.…”
Section: Introductionmentioning
confidence: 99%